Texts and Fragments - Walker, С. В. F.
ersch. 1980; copies, photos; cone of Ashur-nerari I; dupl. of SBH No. 4; bead of Sarduri; BM 81503, OB legal; BM 92539 - KB 4 10-13; BM 136798, OB legal; BM 136872, Achaemenid contract; OB letter.